Primary Cilia in the Skin: Functions in Immunity and Therapeutic Potential - Toriyama, Manami; Ishii, Ken J. (Frontiers in Cell and Developmental Biology, 2021)
The skin is the biggest organ and provides a physical and immunological barrier against pathogen infection. The distribution of primary cilia in the skin of mice has been reported, but which cells in human skin have them has not, and we still know very little about how they change in response to immune reactions or disease. This review introduces several studies that describe mechanisms of cilia regulation by immune reaction and the physiological relevance of cilia regulating proliferation and differentiation of stroma cells, including skin-resident Langerhans cells. We discuss the possibility of primary cilia pathology in allergic atopic dermatitis and the potential for therapies targeting primary cilia signaling.